2007
DOI: 10.1523/jneurosci.1629-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Genetic Patterning of the Embryonic Neuroepithelium Generates GABAergic Interneuron Diversity in the Adult Cortex

Abstract: Cortical pyramidal cells are generated from pallial neuroepithelial precursors, whereas GABAergic interneurons originate in subpallial germinal zones and migrate tangentially to reach the cortex. Using Cre-lox technology in transgenic mice and a series of molecular markers that subdivide the subpallial neuroepithelium into small domains, we fate-map precursor pools and identify interneurons generated from each domain. Cortical interneurons expressing calbindin, parvalbumin, and somatostatin are generated exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
534
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(575 citation statements)
references
References 60 publications
(84 reference statements)
34
534
0
7
Order By: Relevance
“…14,27,28 Within each genetic group, the 13 C-multiplet spectra of glutamate and g-aminobutyric acid (GABA) were comparable, suggesting that the GABA pool is derived directly from the glutamate pool (Supplementary Figure 1) in the neuronal compartment since GABA is primarily produced in GABAergic neurons. 29 Particularly, GABA C3 and C4 contained a doublet (D3,4) that derives from glutamate labeled in carbons 2,3 and in carbons 1,2 and 3. Although this labeling pattern is consistent with metabolism of [5,6,[7][8][9][10][11][12][13] C 3 ]heptanoate to [1,2,3-13 C 3 ]propionyl-CoA followed by entry into the TCA cycle, the identical pattern could occur as a consequence of carboxylation of [1,2,3-13 C 3 ]pyruvate derived from glucose.…”
Section: C-nuclear Magnetic Resonance Spectramentioning
confidence: 99%
“…14,27,28 Within each genetic group, the 13 C-multiplet spectra of glutamate and g-aminobutyric acid (GABA) were comparable, suggesting that the GABA pool is derived directly from the glutamate pool (Supplementary Figure 1) in the neuronal compartment since GABA is primarily produced in GABAergic neurons. 29 Particularly, GABA C3 and C4 contained a doublet (D3,4) that derives from glutamate labeled in carbons 2,3 and in carbons 1,2 and 3. Although this labeling pattern is consistent with metabolism of [5,6,[7][8][9][10][11][12][13] C 3 ]heptanoate to [1,2,3-13 C 3 ]propionyl-CoA followed by entry into the TCA cycle, the identical pattern could occur as a consequence of carboxylation of [1,2,3-13 C 3 ]pyruvate derived from glucose.…”
Section: C-nuclear Magnetic Resonance Spectramentioning
confidence: 99%
“…Transplanted into Adult Neocortex MGE-derived progenitors transplanted into both neonatal and adult mouse cortex have been shown to migrate, survive, and differentiate into several subgroups of cortical interneurons [10,15,17,18]. Relative to progenitors of the cortex, striatum, or hypothalamus, this migration was found to be unique to MGE-derived progenitors [10].…”
Section: Survival and Differentiation Of Mge-derived Cellsmentioning
confidence: 99%
“…Although species differences with primates appear to exist, in rodents and ferrets most cortical interneurons, including the PV and the SST expressing subgroups, originate in the medial ganglionic eminence (MGE) of the subcortical telencephalon [14]. Genetic fatemapping and transplantation studies indicate that within the MGE there is a bias for PV or SST expressing interneurons to originate from ventral or dorsal MGE regions, respectively [15][16][17]. Transplanted MGE cells not only differentiate into mature GABAergic (gamma-aminobutyric-acid-releasing) interneurons, but also form inhibitory synapses that increase GABAergic synaptic transmission onto adjacent pyramidal cells [18] and alter cortical pyramidal neuron plasticity [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the forebrain, GABAergic interneuron diversity of the adult cortex is preceded by, and implemented through, spatial genetic patterning of the embryonic neuroepithelium (e.g., Fogarty et al 2007). Analysis of proneural gene expression in the cerebellar anlage revealed that the early embryonic ventricular epithelium, from which Purkinje cells, and inhibitory cerebellar interneurons arise, is indeed heterogeneous, as documented by a patchy, and only partly overlapping pattern of expression of Mash1, Neurog1, and Neurog2 between embryonic day 10.75 and 13.5 (Zordan et al 2008).…”
Section: Development and Diverentiation Of Cerebellar (Cortical) Inhimentioning
confidence: 99%